2014
DOI: 10.1021/es503144h
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Air Cleaners on Indoor Air Quality in Residences Impacted by Wood Smoke

Abstract: Residential wood combustion is an important source of ambient air pollution, accounting for over 25% of fine particulate matter (PM2.5) emissions in Canada. In addition to these ambient contributions, wood smoke pollutants can enter the indoor environment directly when loading or stoking stoves, resulting in a high potential for human exposure. A study of the effectiveness of air cleaners at reducing wood smoke-associated PM2.5 of indoor and outdoor origin was conducted in 31 homes during winter 2009-10. Day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…These results are in agreement with a number of other studies that have demonstrated consistent reductions in indoor PM 2.5 with HEPA filtration 35 36. Unlike some previous studies, we did not observe any relationships between PM 2.5 and RHI.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with a number of other studies that have demonstrated consistent reductions in indoor PM 2.5 with HEPA filtration 35 36. Unlike some previous studies, we did not observe any relationships between PM 2.5 and RHI.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have assessed the effectiveness of using air cleaners to improve IAQ during smoke haze episodes, based on a reduction of the indoor PM loading [35,41]. Nevertheless, the effectiveness of these devices in reducing human exposure and the associated potential health risks based on the toxic elemental composition of PM indoors remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the effectiveness of these devices in reducing human exposure and the associated potential health risks based on the toxic elemental composition of PM indoors remains largely unknown. Additionally, previous studies reported in the literature [35,41] have been carried out under mid-latitude environmental conditions and thus are not applicable to tropical climatic conditions in SEA, where the smokehaze-impacted PM has unique physico-chemical characteristics [4,5,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…high factor loadings of Al, Si, Ca and Fe are indicative of crustal re-entrained material (Song et al, 2006;Hopke, 1991;Gibson et al, 2013b). Many studies use levoglucosan (1,6-anhydro-β-D-glucopyranose) as an unambiguous chemical tracer of wildfire and residential woodsmoke (Gibson et al, 2010;Ward et al, 2012;Simoneit et al, 1999;Wheeler et al, 2014). Levoglucosan is derived from cellulose burning at temperatures greater than 300 • C (Simoneit et al, 1999;Ward et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%